HUMAN DISABILITIES EMPOWERMENT REFLECTED IN MICHAEL GRACEY’S THE GREATEST SHOWMAN MOVIE - Muhammad Lutfi Nugroho; Ana Widiyanti (Language and Literature Faculty, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2023)
This study examines the portrayal of individuals with disabilities in Michael Gracey's film The Greatest Showman, with a particular focus on the potential elements of human disability exploitation. The film, set in the 19th century, follows the life of P.T. Mr. Barnum and his creation of the Mr. Barnum & Bailey Circus. While celebrated for its vibrant musical numbers and inspirational themes, The Greatest Showman has faced scrutiny for its representation of characters with physical differences. This abstract explores the film's use of stereotypes, the narrative roles assigned to characters with disabilities, and the balance between empowerment and exploitation. By delving into the historical context, audience perception, and real-world impact, this analysis aims to provide a comprehensive examination of how the film handles the delicate subject of disability and whether it contributes to a nuanced portrayal or inadvertently perpetuates exploitative tropes. The abstract also considers the filmmaker's intentions and the broader implications of such portrayals on societal attitudes towards individuals with disabilities.